Some physical measurements and their relationship with the effectiveness of skilled performance for basketball players female in Sulaimani Club - Agag, Safa Mandel; Rajab, Firas Qahtan (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to identify the relationship of some physical measurements with the effectiveness of the skillful performance of the semen basketball players of the Sulaymaniyah club with basketball. The researcher used the descriptive method by the method of correlation. The research sample was chosen by an intentional method from the female athletes of the Sulaymaniyah club in basketball (Minni Basket), who are (10) players The researcher excluded (3) female players for conducting the exploratory experiment on them, and thus the research sample reached (7), on which the basic experiment was conducted. The researcher used some body measurements where the researcher relied on the physical measurements mentioned in the sources and references that are agreed upon by others with the addition of age and weight to these measurements. All these measurements were taken for the research sample from the agreed anatomical points, including (lengths, widths, and perimeters). As for the skill performance test, the researcher used the basketball skills test battery of the American Federation for Health and Recreation, as this battery contains 9 tests and after using the appropriate statistical means, the researcher reached the following conclusions: There is a significant correlation between some physical measurements and the skill performance of basketball. The percentage of the contribution of some body measurements to the performance of skills in basketball was good, which confirms the effectiveness of these measurements in skill performance. The researcher recommended several recommendations to emphasize the importance of anthropometric measurements that showed moral relationships and contribution rates in the performance of basketball skills and work on developing and developing them and taking this into account in developing training programs and plans. There is necessity of adopting anthropometric measurements when selecting sperm players and junior players in basketball and conducting a similar study for the teams of young and advanced students.